Lectotypification of the name Aconitum naviculare (Ranunculaceae) - Agnihotri, Priyanka; Husain, Danish; Husain, Tariq (Phytotaxa, 2015)
Aconitum naviculare was first described by Brühl in Brühl & King (1896) as a variety of Aconitum ferox Wall. ex Ser. i.e. Aconitum ferox var. navicularis. Later on, Stapf (1905) published the new combination, citing Brühl’s var. navicularis as the basionym. This taxon is distributed in the alpine zones of India, China, Nepal and Bhutan. During revisionary studies on the tribe Delphineae from India, it was found that no type has been designated for this taxon. Therefore, a lectotype for A. naviculare is selected here from amongst the original material.